Prevalence and Distribution of Odontogenic Tumors: A Cross-Sectional Hospital-Based Study - Dr Syed Zuhair Mehdi, Dr Samir Azeem Qadri, Dr Usman Manzoor Warraich, Dr Syed Muhammad Faran Ali, Dr Umar Farooq Khan, Dr Hera Nadeem, Dr Nabeel Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Odontogenic tumors (OTs) are uncommon neoplasms of odontogenic origin, representing aheterogeneous group with variable clinical behavior. Their prevalence and distribution show geographical and ethnic variation, emphasizing the need